2021
DOI: 10.3892/mco.2021.2383
|View full text |Cite
|
Sign up to set email alerts
|

Topotecan or other agents as second‑line therapy for relapsed small‑cell lung cancer: A meta‑analysis of randomized studies

Abstract: Small cell lung cancer (SCLC) is exceptionally responsive to chemotherapy and radiotherapy. In relapsed patients, particularly in resistant/refractory cases, the progression of disease occurs rapidly with second-line agents. Topotecan (TOPO), a camptothecin analog, is the only agent able to increase overall survival (OS) compared with the best supportive care alone. However, the efficacy of platinum-based chemotherapy rechallenge or other agents has not been systematically explored. In the present review, publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Clinical trials have reported a wide range of incidence rates for grade 3/4 neutropenia, anemia, and thrombocytopenia with first‐line platinum/etoposide regimens, with or without immunotherapy 32–35 and for second‐line topotecan 36–38 . This study reported that chemotherapy‐induced myelosuppression was prevalent among patients in the real‐world community oncology setting; the most common any‐grade event being anemia, and the most common grade ≥ 3 event being neutropenia.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Clinical trials have reported a wide range of incidence rates for grade 3/4 neutropenia, anemia, and thrombocytopenia with first‐line platinum/etoposide regimens, with or without immunotherapy 32–35 and for second‐line topotecan 36–38 . This study reported that chemotherapy‐induced myelosuppression was prevalent among patients in the real‐world community oncology setting; the most common any‐grade event being anemia, and the most common grade ≥ 3 event being neutropenia.…”
Section: Discussionmentioning
confidence: 88%
“…Clinical trials have reported a wide range of incidence rates for grade 3/4 neutropenia, anemia, and thrombocytopenia with first-line platinum/etoposide regimens, with or without immunotherapy [32][33][34][35] and for second-line topotecan. [36][37][38] This study reported that chemotherapy-induced myelosuppression was prevalent among patients in the real-world community oncology setting; the most common any-grade event being anemia, and the most common grade ≥ 3 event being neutropenia. Our findings are consistent with previous studies in the real-world setting, which have reported that grade ≥ 3 myelosuppressive AEs are common among patients with ES-SCLC treated with chemotherapy (56.6-64.1%) 39,40 grade with inpatient admission = 74.3%).…”
Section: Discussionmentioning
confidence: 99%
“…Even after the introduction of immunotherapy in the first-line setting, the majority of patients with SCLC experiences an inexorable disease progression in less than 12 months ( 4 , 5 ). Unfortunately, effective treatments are not available after disease progression to first-line therapy: topotecan is currently the standard of care, with limited results ( 74 ). These poor outcomes highlight the need for a better molecular knowledge of the disease to develop new therapeutic strategies.…”
Section: Aurora Kinases In Sclcmentioning
confidence: 99%
“…Topotecan, the most widely used second-line agent globally, has limited efficacy and an unfavorable safety profile. 10 , 11 Lurbinectedin, in 2020 became the first drug approval by the FDA in over 20 years to second-line treatment, was conditionally approved based on an objective response rate (ORR) of 35%; however, a randomized study failed to demonstrate OS benefit. 12 No agent is specifically for second-line treatment of relapsed SCLC.…”
Section: Introductionmentioning
confidence: 99%